Training to overcome the speed plateau - Schiffer, J. (New Studies in Athletics, 2011)
The axiom that sprinters are born and not made is still popular with many coaches. However, the widespread notion that speed is an inherited trait that cannot be measurably improved by training is not true. Although there is no doubt that genetic gifts above and beyond the norm are required to become a great sprinter, speed capacities can be maximised using scientifically based training methods. However, training for success in the sprints can be challenging and cornplicated. Elements include high-velocity running, speed endurance, strength and power, flexibility, neuro-muscular programming and mental preparation.